I.i.2.o Minutes - Labour Party (Ireland) (1970)
Minutes of the Administrative Council which took place on 9 Dec 1970 principally concerning: the arrangments for the special delegate conference on electoral strategy; the Administrative Council attitude to amendments to the ‘Statement on Electoral Strategy’ proposed by branches and affiliated unions; and motion on internment. Minutes signed by Brendan Halligan, General Secretary. Also includes: draft minutes signed by Dan Browne, Party Chair; text of amendments proposed by branches and affiliated unions; handwritten organisation committee report; text of motion on interenment; two annotated copies of the ‘Statement on Electoral Strategy’; and one draft copy of the ‘Statement on Electoral Strategy’. (21 pp)